Library 101 as credit-bearing information literacy courses: reduce library anxiety on first-generation college students in Universitas Airlangga / Annisa Nana Nadhea ... [et al.] - Nadhea, Annisa Nana; Yuadi, Imam; Mutia, Fitri; Atmi, Ragil Tri (Faculty of Information Management, 2023)
Library Anxiety is an anxiety that occurs in a person towards the library. It usually happens to new students at a university. This is in line with the data that found that 75 to 85% of students out of 8000 respondents felt anxiety. This anxiety usually occurs due to feelings of fear and embarrassment in students towards the library, both facilities and services. Therefore, there is a need for Credit-Bearing Information Literacy Courses which are courses that will help students learn more about the library at the university. The method used in this article is literature review where it is necessary to collect, evaluate, and analyze articles found in various sources on the internet. The results obtained from this article are the effectiveness of Credit-Bearing Information Literacy Courses in dealing with Library Anxiety in students. It is also exemplified by the Library 101 program in the Universitas Airlangga library which provides an explanation and introduction to students on how to make the most of the facilities and services available at the Universitas Airlangga library.